2019
DOI: 10.1016/j.combustflame.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Study of the importance of non-uniform mass density in numerical simulations of fire spread over MDF panels in a corner configuration

Abstract: The distribution of mass density through the thickness of Medium Density Fiberboard (MDF) panels is known to be non-uniform. A few studies have previously investigated the influence of this non-uniform through-thickness density distribution on the thermal behavior of MDF panels in small-scale tests. This study assesses the significance of this material property on flame spread simulations in a medium-scale setup , namely that of Single Burning Item (SBI) corner fire tests. Simulations are performed using FireF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…Nine layers is therefore considered a good representation of the density profile of MDF. The increase in mass loss rate by 9% for 9 layers and 12% for 18 layers is in good agreement with Zeinali et al [46]. In an independent study, published during the review of this paper, they found that simulations of the heat release rate of MDF in a corner test increases by 20% when taking into account the non-uniform density.…”
Section: Influence Of Non-uniform Density At Two Different Moisture Csupporting
confidence: 89%
“…Nine layers is therefore considered a good representation of the density profile of MDF. The increase in mass loss rate by 9% for 9 layers and 12% for 18 layers is in good agreement with Zeinali et al [46]. In an independent study, published during the review of this paper, they found that simulations of the heat release rate of MDF in a corner test increases by 20% when taking into account the non-uniform density.…”
Section: Influence Of Non-uniform Density At Two Different Moisture Csupporting
confidence: 89%
“…The effect of mass transpiration (i.e., blockage of convective heat transfer with increasing mass transfer rates) has been reported experimentally in the past for upward spread scenarios over vertical PMM slabs [20]. Additionally, the inclusion of mass transpiration effects has also been considered when modelling flame spread using the approaches based on the law of the wall (e.g., [50]), based on the stagnant film theory (e.g., [12]) as well as on the convective heat transfer model of FireFOAM 2.2.x (e.g., [61][62][63]).…”
Section: Blowing Effectmentioning
confidence: 99%
“…whereṁ pyrol is the mass loss rate due to pyrolysis of the solid fuel,q c, laminar = −αρc p ∂T ∂s is the convective heat flux calculated based on the molecular thermal diffusivity (positive for heating up of the wall, i.e., T g > T w ), s is the direction normal to the wall,q c, threshold is a threshold value (e.g., in the range of 0.5 kW/m 2 [61]),q c, f lame is the maximum value (e.g., in the range of 15 kW/m 2 [61]) of the convective heat flux without mass transfer (i.e., calculated based on an average temperature difference and a convection coefficient value) and f blowing is a correction for the 'blowing' effect (i.e., see Section 4.2). This approach, does not directly take into account the local properties of the flow and considers that the convective heat fluxes remain relatively constant with elevation (i.e., the convective heat transfer coefficient, h, is not calculated).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The approach also considers mass transpiration effects which tend to reduce the convective heat flux in regions where there is mass transfer. Consideration of mass transpiration effects, while modelling of convective heat transfer, has been included to a certain extent in the literature in the past (e.g., [8,9,10]) but is not necessarily standard practice in fire modelling (e.g., it is not considered by default in FDS [11]). Additional modelling aspects can also be important with respect to accurate (convective) heat flux predictions.…”
Section: Introductionmentioning
confidence: 99%